(untitled) (Acta Entomologica Serbica, 2019)
A landmark-based geometric morphometric method was employed to delimitate two morphologically closely-related species of the hoverfly Merodon natans species group based on wing parameters. The studied species, Merodon natans and M. pulveris, were successfully determined using this method. Analyses revealed a significant difference in wing size and shape between individuals of the two species, thereby proving that these are two distinct species, even though, morphologically very similar. Discriminant and cluster analyses also uncovered a subtle difference in wing shape between M. pulveris populations, indicating intraspecific differentiation with potential conservation implications. The results of the morphological study were supplemented with known distribution data of the investigated species.